Optimization and Enhancement of Tensile Strength and Elongation at Failure in Basalt/Glass Fiber Polymer Composites With MWCNTs + SiO2 Hybrid Nanofillers Using Response Surface Methodology - T. Sathish; V. Boobalan; Jayant Giri; Ahmad O. Hourani; A. Johnson Santhosh; Faouzi Nasri (Engineering Reports, 2025)
ABSTRACT This study focuses on optimizing the tensile performance of basalt/glass fiber‐reinforced polymer composites enhanced with hybrid nanofillers, comprising equal proportions of multi‐walled carbon nanotubes (MWCNTs) and silicon dioxide (SiO2). The nanofiller content is evaluated at weight percentages of 0%, 1%, and 2%. Using response surface methodology (RSM), the research investigates the interactive effects of three key parameters: filler weight (0%–2%), molding pressure (5–15 MPa), and sonication time (10–30 min) on the mechanical performance of the composites. A Box–Benkhen design was adopted to develop predictive models and establish optimal processing conditions for maximizing the mechanical properties. The tensile test (as per ASTM D 638 standard) and scanning electron microscopy (SEM) were performed. It was found that filler weight plays a dominating role in the tensile performance of hybrid nanocomposites, followed by molding pressure and sonication time. A predictive mathematical model was developed for each response. The maximum tensile strength of 267 MPa and an elongation at failure of 2.25% were achieved at a filler weight of 1%, molding pressure of 15 MPa, and sonication time of 30 min, corresponding to run order 16. The hybrid nanofillers synergistically enhance the load transfer efficiency and interfacial bonding, as observed through microstructural analysis using SEM. Statistical analysis validated the accuracy and reliability of the developed models, demonstrating robust correlation coefficients between actual and predicted values. The results highlight the potential of RSM as a strong tool for optimizing hybrid nanocomposite properties, paving the way for advanced material design in structural applications.